Синтез релейной системы четвертого порядка методом N-i переключений в контексте теоремы об N интервалах - Дерец, Александр Леонидович; Садовой, Александр Валентинович (НТУ "ХПИ", 2013)
Correlation for magnitude of performing input step with parameters of sliding mode control fourth-order system was obtained by the N-i switches method, which provides time-optimal transient. Steadiness of sliding mode was checked out in analytical way.
Keywords: электромеханические системы; релейные регуляторы; системы подчинённого регулирования; величина задающего воздействия; адаптивные цифровые системы управления; ресурсы контроллера